Rice Food Security Strategy in of Covid 19 Era East Oku Regency, Indonesia - Ema Pusvita; Ardi Asroh (Budapest International Research and Critics University, 2022)
The rice food security strategy for COVID-19 era in OKU Timur Regency. The purpose of research to analyze problems in COVID-19 era pandemic fast and accurate. So set a strategy to overcome the risk of food insecurity in OKU Timur Regency. The research method used historical research method and used time series data from 2010 to 2020. Using a SWOT questionnaire, a list of questions had been compiled to be distributed to 50 respondents. The results of the study found that the rice food security strategy in the COVID-19 era in OKU Timur Regency could be carried out by an IFAS strategy of 3.08 and an EFAS of 3.01 with a grand strategy in quadrant I, namely a concentration strategy through vertical integration. SWOT matrix was generated by SO strategy: construction of food barns, food diversification, and role of BULOG. WO: training of the young generations on modern farming, subsidy for production inputs, and utilization of human resources to process natural resources. ST: government policy to sets the price of rice and production input prices. WT: managing rice supplies, using organic production inputs, socializing entrepreneurship in rice.